“Innovare” program, based on b-learning, to improve the level of achievement of the communication area for secondary school students - Trujillo, 2019 (SCIÉNDO INGENIUM, 2022)
The purpose of the study was to determine if the 'INNOVARE' program, based on b-learning, influences the improvement of the level of achievement of learning in the area of ​​communication of the students of the 5th grade of secondary education of the I.E. 81001 Republic of Panama in the year 2019. A quasi-experimental design was used, with a population of 120 students and a sample of 60 students, 30 for the control group and 30 for the experimental group. For data analysis, the Wilcoxon signed rank test was applied. The "Innovare" program, based on b-learning, comprises a set of learning sessions, using the "Aulantic" virtual platform. The test statistic confirms that in the experimental group YES there is a significant difference (significance < 1%) between the pre-evaluation and the post-evaluation due to the application of the Innovare program; while in the control group there is NO significant difference (significance > 5%) between both tests due to the NO application of the Innovare program. In conclusion, the Innovare program, based on b-learning, YES has influenced the improvement of the level of achievement of learning in communication of the students of the 5th grade of secondary education of the I.E. 81001 Republic of Panama in the year 2019.
Keywords: Innovare program; b-learning; oral expression; comprehension of texts; production of texts